Kolaborasi Kampus dan Sekolah dalam Meningkatkan Literasi dan Numerasi melalui Edukasi Berbasis Teknologi - Sari, Rafika; Abdillah, Sabiq; Ayu, Visca Anindha; Agati DJ, Sharlen Taurisya; Manullang, Nathasya Grisella; Cahyani, Dwi Sinta; Novarizal, Safarin (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
The 8th Batch of the Kampus Mengajar Program at SMPN 5 Cikarang Utara aimed to improve students’ literacy and numeracy through collaborative and innovative approaches. Implemented activities included teaching assistance, weekly reading habits, educational programs such as